Rational toral ranks in certain algebras - Yasusuke Kotani; Toshihiro Yamaguchi (International Journal of Mathematics and Mathematical Sciences)
We calculate the rational toral ranks of two spaces whose cohomologies are isomorphic and note that rational toral rank is a rational homotopy invariant but not a cohomology invariant.